A two-dimensional Fe-doped SnS2 magnetic semiconductor. Issue 1 (December 2017) - Li, Bo; Xing, Tao; Zhong, Mianzeng; Huang, Le; Lei, Na; Zhang, Jun; Li, Jingbo; Wei, Zhongming
Abstract Magnetic two-dimensional materials have attracted considerable attention for their significant potential application in spintronics. In this study, we present a high-quality Fe-doped SnS2 monolayer exfoliated using a micromechanical cleavage method. Fe atoms were doped at the Sn atom sites, and the Fe contents are ∼2.1%, 1.5%, and 1.1%. The field-effect transistors based on the Fe0.021 Sn0.979 S2 monolayer show n-type behavior and exhibit high optoelectronic performance. Magnetic measurements show that pure SnS2 is diamagnetic, whereas Fe0.021 Sn0.979 S2 exhibits ferromagnetic behavior with a perpendicular anisotropy at 2 K and a Curie temperature of ~31 K. Density functional theory calculations show that long-range ferromagnetic ordering in the Fe-doped SnS2 monolayer is energetically stable, and the estimated Curie temperature agrees well with the results of our experiment. The results suggest that Fe-doped SnS2 has significant potential in future nanoelectronic, magnetic, and optoelectronic applications. 2D materials can be doped with magnetic atoms in order to boost their potential applications in spintronics. Here, the authors fabricate Fe-doped SnS2 monolayers and show that Fe0.021 Sn0.979 S2 exhibits ferromagnetic behaviour with perpendicular anisotropy at 2 K, and a Curie temperature of 31 K.